Pengaruh Citra Destinasi dan Fasilitas Wisata terhadap Niat Berperilaku Melalui Kepuasan Sebagai Variabel Intervening (Studi pada Pengunjung Museum Kereta Api Ambarawa) - Lintang Tyas Kristanti; Naili Farida (Universitas Diponegoro, 2016)
This research is motivated by the fluctuation of the Ambarawa Railway Museum’s revenues. The objective of this study was to determine the influence of destination image and tourism facility on behaviour intention with satisfaction at the Railway Museum Ambarawa. This type of research is explanatory research, with data collection through questionnaires and interviews. The sampling technique used purposive sampling technique. The sample in this study amounted to 100 respondents who are adult visitors Railway Museum. This study used the analytical techniques of qualitative and quantitative analysis. Quantitative analysis using validity test, reliability test, the coefficient of correlation test, simple and multiple regression analysis, the coefficient of determination test, significance test (t test) in one direction, and the second stage regression. The results show that there is positive influence of destination image and tourism facility partially on satisfaction, and satisfaction has positive influence on behaviour intention. Based on the results of the regression analysis of 2 phase, it is known that variable destination image and tourism facilities influence on satisfaction, each coefficient is 0.205 and 0.549. Further satisfaction variables affect behaviour intention with the coefficient is 0.549.